ANDALAS UNIVERSITY BRANDING STRATEGY: INSTITUTIONAL HISTORY IDENTIFICATION IN BUILDING IDENTITY AS AN ENTREPRENEURIAL CAMPUS - puspita, yesi; Putra, Robi Jaya; Syafiola, M.Fedro (Jurnal Ranah Komunikasi, 2025)
Universitas Andalas (Unand) as one of the oldest universities in Indonesia has a long history in shaping institutional identity rooted in local values and national spirit. In the context of the changing landscape of higher education that is increasingly competitive and innovation oriented, Unand has renewed its identity as a form of adjustment to the demands of the times. This research aims to examine the dynamics of Unand's institutional identity renewal by tracing its relationship to institutional history, managerial strategies, and the entrepreneurial spirit carried in its new narrative. A descriptive qualitative approach was used to identity of Andalas University from the history and local wisdom of Minangkabau so as to obtain strong branding. The results of the study show that this process not only reflects efforts to strengthen institutional branding, but also becomes part of strategic management in building a responsive, innovative, and globally competitive university. This image refresh underlines Unand's new orientation that is not separated from its history, but based on the entrepreneurial spirit as the foundation of future institutional development